As relações de cuidado “dia e noite” em um CAPS infantojuvenil III na perspectiva de profissionais e do usuário - Jozefczyk, Andréia Martinez (2021)
The present study inserts in the field of debates of children and adolescents' mental health, more specifically, in the tensionings between different positionings in which are considered as "psychic subjects and rights" and those that practise the tutelage and subjection; in the relationship between adults with children and young people and; between the so-called asylum modes, with the characteristics of assisted's isolation and passiveness towards the medical knowledge and psycosocials, with characteristics of the integration into the social life and the assisted's participation over the scheduling that concerns them. The context of COVID-19 pandemic was also a considered dimension of this study that searched for characterizing and analysing the relationship between day and night care (night reception) offered to the children and young people in one of the seven Psychosocial Attention Centres of children and young people III (CAPS IJ III) in the municipality of São Paulo - SP, Brazil, through the professionals and user's perspective. Ten actors participated in different segments of the same CAPS IJ III: management, team, family and user. It was applied, as a methodological resource, the Institutional Analysis, specifically, the Intervention Research, through the following procedures: semi-structured with family, team, user and management, rounds of conversations with professionals and field diary. For the selection and analysis of the material, an integration of different perspectives from the participants was made referring to the night reception care, according to the diversity practices. Among the results are that cares are intensified 24 hours at CAPS IJ III and characterised in the following ways: 1. Basic cares and body cares (food, personal hygiene and sleep); 2. Relations of participatory and inventive care (listening, give way to the children and young people's expressiveness - in the ludic way, artistic; creative relations for tense and conflicting situations and to enable the participation and empowerment); 3. The care for the articulation of the sectorial and intersectorial network. The care described in 1 is aligned with "social cares", related to life and maternity guarantee and in 2 and 3, are aligned with the extended clinic, as in the perspective that takes the assisted subject active and participant of his/hers care, as that who considers the transdisciplinary practices and in the network. Such cares enable, according to the itinerary of a young person that has been in a night reception, the psycosocial, that was brought: 1. Reinventions to the user's participation although in a situation considered "critical limit"; 2. Alternative scheduling to the hospital intervention; 3. Territorial bonding of a longitudinal mode and in sector network. Notice that, according to the participants speeches, not all actions of care – despite the users' intense situations – that the same need night reception. Since that there are cares that are beyond these devices and that they refer to other CAPS IJ resources and, also, those concerning to the territorial network; including access to the basic rights and of citizenship, that became more scarce during the pandemic. Finally, it stands out the need for future studies, where the medication practice can be explored – associated to the professionals to the care at the night reception – as it can be referred to a pragmatic care (technical procedure concentrated on the medical knowledge), as to the care in an extended clinic